Pengukuran Kualitas Pelayanan Publik Berdasarkan Permenpan No 14 Tahun 2017 pada Puskemas Sanggalangi’ Kabupaten Toraja Utara - Pasulu, Isak; Pali, Elisabet (UKI Toraja Press, 2021)
Public services quality as measured by community satisfaction as service users are the main benchmar to determining the success of public organizations in carrying out their duties. Focus of this research is community satisfaction regarding the quality of public services at the Puskesmas Sanggalangi' Toraja Utara. The method used is descriptive quantitative. The sampling technique was incidental sampling, with a sample of 100 respondents. The quality of public services was measured Permenpan-RB Indonesia Number 16 of 2014 concerning Guidelines for Survey of Community Satisfaction on Public Service Delivery. The results of the analysis regarding the quality of public services at the Sanggalangi Public Health Center in North Toraja Regency in 2020 obtained an IKM value of 82.67 which means that public satisfaction with the quality of public services at the Puskesmas Sanggalangi' Toraja Utara is good category based on Permenpan-RB No. 14 of 2017.